Zastosowanie rachunku cyklu życia produktu w działalności proekologicznej przedsiębiorstw - Szczypa, Piotr (Application of Product Life Cycle Costing in Pro-Ecological Activity of Enterprises, 2006)
Nowadays it becomes more popular for enterprises to consider pro-ecological aspects while implementing their strategies. These aspects should be considered with reference to the whole life cycle of a product. That is the reason for enterprises to analyse their revenues and costs with reference to pro-ecological factors at every stage of a product life cycle.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 398-404